1998
DOI: 10.3208/sandf.38.special_193
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuge Modeling of a Single Pile Subjected to Liquefaction-Induced Lateral Spreading

Abstract: The 1995 Hyogoken-Nambu earthquake caused widespread liquefaction on the reclaimed islands in Kobe. The surrounding quay walls moved significantly towards the sea leading to horizontal movement of the soil behind the quay walls. Investigation of the piles installed in the reclaimed islands clearly showed the need for piles in such grounds to be designed taking into account the effects of lateral spreading of liquefied soils. The present study is aimed at establishing a simple design method for pile foundations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The effects of large lateral soil movement, especially liquefaction-induced lateral spreading of soil, on the failure and deformation of the piles have been experimentally investigated using geotechnical centrifuges by many researchers (e.g. Abdoun & Dobry, 1998, Horikoshi et al, 1998, Satoh et al, 1998, Takahashi et al, 1998. In these researches, shaking tables were used to simulate the ground motions during earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of large lateral soil movement, especially liquefaction-induced lateral spreading of soil, on the failure and deformation of the piles have been experimentally investigated using geotechnical centrifuges by many researchers (e.g. Abdoun & Dobry, 1998, Horikoshi et al, 1998, Satoh et al, 1998, Takahashi et al, 1998. In these researches, shaking tables were used to simulate the ground motions during earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of soil strength and stiffness due to liquefaction may develop large bending moments and shear forces in piles founded in liquefying soil, leading to pile damage. The significance of liquefactionrelated damage to pile foundations has been clearly demonstrated by the major earthquakes that have occurred during past years such as the Niigata, 1964Alaska, 1989Loma-Prieta, and 1995 There remain many uncertainties in the mechanisms involved in pile-soil-structure interaction in liquefying soil, although the data recorded during the 1995 Hyogoken-Nambu earthquake, shake table tests ͑e.g., Ohtomo 1996;Tamura et al 2000;Yasuda et al 2000;Mizuno et al 2000;Nakamura et al 2000͒, and centrifuge tests ͑e.g., Dobry et al 1995;Abdoun et al 1997;Horikoshi et al 1998;Wilson et al 1999;Wilson et al 2000͒ provide an insight into the mechanism of pile-soil-structure interaction in liquefying soil.…”
Section: Introductionmentioning
confidence: 99%
“…It is overall confirmed that the kinematic loading resulted from the lateral displacement is the major cause of large lateral displacement of footings in the SPSQ system (Bouckovalas and Chaloulo;2014). In particular, Horikoshi et al (1998) found that the input motion significantly affects the lateral displacement of piles, while the effect of frequency content of input motion is not clarified. Tazoh et al (2008Tazoh et al ( , 2010 reported that the inclined piles have smaller bending moments but greater axial forces than vertical piles and are more effective than vertical piles in restricting lateral displacement of superstructures subjected to the lateral displacement after the failure of quay wall.…”
Section: Introductionmentioning
confidence: 95%
“…These model tests investigated various influencing factors, including the pileto-wall distance, thickness of overlaying non-liquefiable layer, shaking direction, the mass of the footing, input motion, wall type (i.e. either sheet-pile or gravity-type quay wall), and the pile rake angle (Sato, 1994;Horikoshi et al, 1998;Sato et al, 2001;Tanimoto et al, 2003;Tazoh et al, 2005;Tang et al, 2014;Liu et al, 2017;Su et al, 2016;Motamed et al, 2009Motamed et al, , 2013. It is overall confirmed that the kinematic loading resulted from the lateral displacement is the major cause of large lateral displacement of footings in the SPSQ system (Bouckovalas and Chaloulo;2014).…”
Section: Introductionmentioning
confidence: 99%